The Role of Profitability and Investment Opportunities Set in Determining Dividend Policy: Evidence from the Consumer Non-Cyclicals Sector - RENGGANIS, RR. Maria Yulia Dwi; ARIANI, Ni Komang (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:This study aims to test and obtain empirical evidence of the effect of profitability and investment opportunity set on dividend policy in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange.Methodology:The population of this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sample in this study was 19 non- cyclical consumer sector companies. The research technique for this sample is purposive sampling. The data analysis used in this study is multiple linear regression analysis.Findings:Profitability has a positive and significant effect on dividend policy, indicating that companies with high earnings tend to be capable and willing to distribute dividends as a signal of good prospects. In addition, the investment opportunity set (IOS) also shows a positive effect, although the initial hypothesis predicted a negative relationship. This suggests that companies with high investment opportunities can still distribute dividends, especially if they have adequate access to external financing.Implication:The results of this study have implications for company management that profitability and investment opportunity set (IOS) must be strategically managed in determining dividend policy. This finding enriches the literature on dividend policy, particularly in the context that IOS does not necessarily act as a barrier to dividend distribution.